“MODEL ANAK ANGKAT” DALAM PENINGKATAN KUALITAS SEKOLAH (KASUS SEKOLAH DASAR MUHAMMADIYAH CONDONGCATUR, YOGYAKARTA) - Tatang M Amirin; Suyud M D; Nurlina Marliyasari Asih (Jurnal Internasional Manajemen Pendidikan, 2010)
Several models has been developed in Indonesia in improving the school quality.One of them is a model of developing one school as a core-school (“sekolah inti”), from which the other surrounding (a cluster) schools (named impacted-school or “sekolah-imbas) are expected to get its impact (“imbas”) through “sekolah inti dan imbas”cooperation, in which the core-school became a development center for a cluster of schools. The core-school is a selected school which has higher quality resources, especially in human resources, than the other surrounding schools. This school staffs, after experienced a special training, has been given responsibility to pull up the other school staffs in improving school quality. A“sekolah inti-imbas model”like has been developed in Muhammadiyah schools, a private schools which is belong to Muhammadiyah organization, in Yogyakarta. This model firstly developed by Muhammadiyah Primary School at Sapen, Yogyakarta. Several Muhammadiyah primary schools then affiliated with and took the name of this school as a “benchmark”for public reputation and trust. One of them is Muhammadiyah Primary School at Condongcatur which is named as “Muhammadiyah Sapen Primary School at Condongcatur.”Nowaday, this school, after releasing from Sapen “subordination,”become a “father figure” school, bringing the other lower level quality and near collapsed Muhammadiyah schools, even a junior high school, to be sustained and higher quality schools. In other words, several Muhammadiyah schools in Yogyakarta have developed a “fosterparenting” model to “move up together”to be the best schools. Keywords: Muhammadiyah schools,”model anak angkat” (fosterparenting model), school quality improvement.